تحليل محتوى كتاب اللغة العربية بالمدرسة الثانوية الإسلامية على أساس الإطار المرجعي الأوروبي المشترك (CEFR) - Solikin, Hadi; Asrori, Imam; Rosyidi, Abdul Wahab (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
In recent years, the Common European Framework of Reference (CEFR) for Languages, which is a European reference in language issues, has received a lot of attention from foreign language learning activists, including Arabic teachers in various countries. Meanwhile, Arabic language teachers at Islamic schools in Indonesia prefer to use an independent curriculum based on the Decree of the Minister of Religion No. 183, 2019. This study attempts to analyze the content of Arabic books at Madrasah Aliyah (MA) which are based on KMA 183 and compare them with CEFR which focuses on 4 language skills: listening, reading, speaking, and writing. This study is a qualitative research by using a descriptive analytical approach and documentation techniques in data collection strategies. The result of this study is to classify language skill contents into the CEFR classification as follows: (1) the language skills content in the Class X MA Arabic language book fluctuates between levels A2 and B1, (2) while for class XI MA it is at levels A2, B1, and B2, (3) and for class XII MA it ranges between levels A2, B1, and B2 as well. From these results it can be understood that a small part of the contents of Arabic books at Madrasah Aliyah (MA) are at the beginner level (A2), while most of them are at the intermediate level B1 and B2, while normally the CEFR standard in language learning for the intermediate level must be at levels B1 and B2.